2020
DOI: 10.1155/2020/7265941
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Process Parameters on Surface Profile Accuracy in Single‐Point Incremental Sheet Forming of AA1050‐H14 Aluminum Alloy

Abstract: Single-point incremental forming is an innovative flexible and inexpensive technique to form sheet products when prototypes or small batches are required. The process allows complex geometries to be produced using a computer numerical control machine, eliminating the need for a special die. This study reports on the effects of four important single-point incremental forming process parameters on produced surface profile accuracies. The profile accuracy was estimated by measuring the side angle errors and surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…A significant problem occurring during the forming of aluminium and its alloys is galling, which significantly affects the quality of manufactured products, as well as reducing the durability of the tools [189,190]. However, the tribological properties of aluminium and its alloys, i.e., a high coefficient of friction, and the tendency to seize significantly limit their incremental forming, in which there are high contact pressures [191][192][193]. One of the ways to improve the surface quality of these sheets is to optimise the processing strategy, including the values of the processing parameters.…”
Section: Surface Finish 61 Process Parametersmentioning
confidence: 99%
“…A significant problem occurring during the forming of aluminium and its alloys is galling, which significantly affects the quality of manufactured products, as well as reducing the durability of the tools [189,190]. However, the tribological properties of aluminium and its alloys, i.e., a high coefficient of friction, and the tendency to seize significantly limit their incremental forming, in which there are high contact pressures [191][192][193]. One of the ways to improve the surface quality of these sheets is to optimise the processing strategy, including the values of the processing parameters.…”
Section: Surface Finish 61 Process Parametersmentioning
confidence: 99%
“…In SPIF different materials like metals (Aerens et al, 2010), brass alloys (Fritzen et al, 2018), polymers (I. , shape-memory foams, sandwich panels, and composite materials have been formed which are used in different industries like medical implants (Isabel Bagudanch et al, 2015), transportation, automobile, and aerospace industries. Initial sheet thickness is a crucial parameter in SPIF and has significant effects on other parameters such as tool diameter, forming force, spring back, wall angle, wall thickness, thinning ratio forming height, and so on are affected by it (Dabwan et al, 2020;Han et al, 2013). So sheet material properties can be seen as the base upon which all other parameters are selected, as the undeformed sheet thickness increases the formability also increases (Kopac & Kampus, 2005).…”
Section: Sheet Materialsmentioning
confidence: 99%
“…High geometric accuracy and surface quality have been achieved with respect to lowstrength metal alloys. For instance, Dabwan et al [1] has applied SPIF on AA1050-H14 aluminum alloy at room temperature which revealed excellent geometric accuracy and surface quality. However, the study commented that the step trainsition region indicated highly deformed region which increased the geometric inaccuracy and waviness error.…”
Section: Introductionmentioning
confidence: 99%